Determining the efficiency of restored photovoltaic modules under natural lighting conditions - Shvedchykova, Iryna; Trykhlieb, Andrii; Trykhlieb, Serhii; Demishonkova, Svitlana; Pavlenko, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is thin-film photovoltaic modules without physical damage, manufactured by CIGS technology, affected by potential-induced degradation, after restoration. The possibility of improving the efficiency of the array of restored photovoltaic modules of the Q.SMART UF L 105 type has been established experimentally, under natural lighting conditions, up to 50 % and higher with respect to the new reference photovoltaic panel. An expression for evaluating the efficiency of restored photovoltaic panels has been derived. It is proposed to use a relative indicator – the efficiency index, which is calculated based on the specific generation data of photovoltaic modules. During the experiment, photovoltaic panels were connected to the OpenSCADA dispatch control and data collection system. Experimental studies were carried out in the autumn-winter period under three weather scenarios: clear day, variable cloudiness, continuous cloudiness. The specific monthly generation of photovoltaic modules was defined as the amount of energy produced during the month per unit of power, which is 100 W. During the experiment, minute and hourly fluctuations in the generation of photovoltaic modules were recorded. Based on the results of calculating the efficiency index, it was concluded that the generation of electrical energy by exhausted photovoltaic modules after restoration under real operating conditions allows for the possibility of their secondary application. The results of the research could be used as a basis for evaluating the efficiency of restored photovoltaic modules while the resulting statistical data on their performance could be used to devise rules and standards for the secondary application of exhausted photovoltaic panels